Mortality and Threats to Hanuman Langurs (Semnopithecus entellus Entellus) in and around Jodhpur (Rajasthan) - Ram, Chena; Sharma, Gautam; Rajpurohit, L. S. (Indian Forester, 2015)
Many factor like habitat destruction due to anthropological reason and climatic condition, electrocution, urbanization, natural predators and Infanticide affects the life span of free ranging langur and leads to artificial deathtohanumanLangur. Inour studyoutof totalobserveddeath(7.8%of total langur population) of langur, 35.7 % was due to only electrocutions and 23.6% due to road accident, 16% due to Natural predator, 22.2% due to unknown cause and 2.5% due to infanticide). The results suggest that electrocution is a major cause of death of free ranging langur.